Studi Kasus Penyebaran Panas Bumi Non Vulkanik Sekitar Sumber Air Panas Hantakan, Kalimantan Selatan - Simon Sadok Siregar; Sri Cahyo Wahyono; Nurlina Nurlina (Lambung Mangkurat University Press, 2011)
The measurement had been conducted about an identification ofgeothermal fluid in heated pool tourist territory Murung B village, Hantakan subdistrict,Hulu Sungai Tengah regency. This research aims to find out litolhogy soil/rock in thearea around the hot water pool, knowing the value detainees soil type/rock containinggeothermal fluid and determine the distribution methods of arrest. Electrodeconfiguration used method Schlumberger (1D) and pole-pole (3D). Referring to theresults of the processing of Progress program can be made two-dimensional crosssectionto find out manually litolhogy coating model soil / rock which then correlatedwith ploting 3D models of Res3Dinv program. Geoelectric research results indicatethat the geothermal fluid in the surrounding in heated pool tourist territory, Hantakansubdistrict, Hulu Sungai Tengah regency has a range of resistance values between108 - 663.60 Ωm, in the depths of 14.67 - 90.2 m from the point G-3 - G-1. Geothermalfluid distribution direction at the research area is spread laterally from the point G-3 -G-1 where a layer of sand mixed with clay and granite rock fragments as an area ofconductive layers and clay as cover.